2019
DOI: 10.1101/585315
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Long Pentraxin 3 (PTX3) Suppresses Immunity to Cutaneous Leishmaniasis by Negatively Regulating Th17 Response

Abstract: 25 26 2 27 Abstract:28 The long Pentraxin 3 (PTX3), a soluble pattern recognition molecule, plays a critical role 29 in inflammation, tissue repair and wound healing. Here, we show that PTX3 regulates 30 disease pathogenesis in cutaneous leishmaniasis (CL). PTX3 expression is increased in 31 active skin lesions in patients and mice during CL, with higher levels being expressed in 32 individuals with severe disease. PTX3 deficient (PTX3 -/-) mice were highly resistant to L.33 major infection and the enhanced re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…The subsequent deletion of PTX-3 gene in the C57BL/6 mice resulted in enhanced resistance (reduced lesion size and parasite burden) following L. major infection. This was associated with significantly enhanced Th17/IL17 response, which we showed might be responsible for the enhanced resistance to L. major infection [125]. This study suggests that neutralization of PTX-3 in infected individuals may potentially reduce the severity of the disease.…”
Section: Modulation Of Host Moleculesmentioning
confidence: 53%
See 1 more Smart Citation
“…The subsequent deletion of PTX-3 gene in the C57BL/6 mice resulted in enhanced resistance (reduced lesion size and parasite burden) following L. major infection. This was associated with significantly enhanced Th17/IL17 response, which we showed might be responsible for the enhanced resistance to L. major infection [125]. This study suggests that neutralization of PTX-3 in infected individuals may potentially reduce the severity of the disease.…”
Section: Modulation Of Host Moleculesmentioning
confidence: 53%
“…Indeed, we found significantly higher levels of PTX-3 expression in skin biopsies of patients with active skin lesion caused by L. braziliensis infection. Treatment with chemotherapy significantly suppressed the expression of PTX-3 in these patients [125]. In another recent study, we showed that Semaphorin-3E (Sema3E), a host molecule involved in axon guidance, was increased at the site of L. major infection.…”
Section: Modulation Of Host Moleculesmentioning
confidence: 75%